Loneliness mediates the relationships between perceived neighborhood characteristics and cognition in middle‐aged and older adults. (6th July 2021) - Yu, Xiaohui; Yang, Jiulong; Yin, Zhenhua; Jiang, Wenjie; Zhang, Dongfeng
Abstract: Objectives: We aimed to examine whether loneliness mediates these associations between perceived neighborhood characteristics and cognition among middle‐aged and older adults. Methods: Data from wave 10 (2010–2012) to wave 13 (2016–2017) of the Health and Retirement Study were analyzed. Perceived neighborhood characteristics were self‐reported. Loneliness was measured by Revised University of California Los Angeles (R‐UCLA) Loneliness Scale. Cognition was evaluated by the modified version of Telephone Interview for Cognitive Status. Baron and Kenny's causal steps and multiple linear regression models based on Karlson/Holm/Breen (KHB) method were used to examine the mediating effect. Results: At baseline, 15, 142 participants had no cognitive impairment, and 11, 413 individuals were finally included in our analysis after 6‐year follow‐up. Multiple linear regression models suggested that lower perceived neighborhood physical disorder ( β  = 0.073, p  = 0.033) and greater perceived neighborhood safety ( β  = 0.350, p  = 0.009) were associated with better cognition. KHB test identified the significant mediating effect of loneliness on the relationships between perceived neighborhood physical disorder ( β  = 0.011, p  = 0.016) and perceived neighborhood safety ( β  = 0.023, p  = 0.026) and cognition. Conclusions: Perceived neighborhood characteristics are associated with cognition among middle‐aged and older American adults. Loneliness mediated associations between perceived neighborhood physical disorder and perceived neighborhood safety and cognition. Key points: Perceived neighborhood characteristics were associated with cognition among middle‐aged and older American adults. Loneliness mediated associations between perceived neighborhood physical disorder, perceived neighborhood safety and cognition. The public health interventions aimed at preventing cognitive decline may benefit greatly via focusing on reducing loneliness among middle‐aged and older adults.